Bank risk determinants in Latin America - Mari\~na Martínez-Malvar; Laura Baselga-Pascual (Risks, 2020)
Systemic Banking crises are a recurrent phenomenon that affects society, and there is a need for a better understanding of the risk factors to support prudential regulation and reduce unnecessary risk intake in the financial system. This paper examines the main bank risk determinants in Latin America. The period analysed covers the timespan from 1999 to 2013, including the systemic banking crisis episodes in Argentina (2001-2003) and Uruguay (2002-2005). We apply a new data-driven comparable methodology to classify and select commercial banks from the sample. We study bank risk proxied by the Z-score. We use the system-GMM estimator as our main empirical analysis method. According to our results, well capitalized, liquid, and traditional commercial banks are less risky. We perform robustness tests by applying OLS, and the results resemble our original model.
Keywords: G21; G32; L11; 330; Latin America; financial risk and risk management; banks and depository institutions; bank risk management; emerging markets